1996
DOI: 10.1115/1.2822697
|View full text |Cite
|
Sign up to set email alerts
|

Transport Phenomena During Resistance Spot Welding

Abstract: Unsteady, axisymmetric transport of mass, momentum, energy, species, and magnetic field intensity with a mushy-zone phase change in workpieces and temperature, and magnetic fields in electrodes during resistance spot welding, are systematically investigated. Electromagnetic force, joule heat, heat generation at the electrode–workpiece interface and faying surface between workpieces, different properties between phases, and geometries of electrodes are taken into account. The computed results show consistencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 6 publications
0
29
0
Order By: Relevance
“…At the same time, the viscosities from T f0. 4 to T 1 decrease in an exponential function, and may result in a sharp decrease near T f0.4 , and also may cause numerical instabilities. Based on the above two concerns, two variations of the benchmark model were also investigated in this research, as shown in Figures 1 and 2. …”
Section: Flow Model In Mushy Zonementioning
confidence: 97%
See 1 more Smart Citation
“…At the same time, the viscosities from T f0. 4 to T 1 decrease in an exponential function, and may result in a sharp decrease near T f0.4 , and also may cause numerical instabilities. Based on the above two concerns, two variations of the benchmark model were also investigated in this research, as shown in Figures 1 and 2. …”
Section: Flow Model In Mushy Zonementioning
confidence: 97%
“…However, it is very difficult to reveal the fluid flow in the nugget with experimental means since the nugget area is not directly observable. In 1996, Wei [4] developed a dimensionless finite difference (FD) model to analyze the flow field in a nugget. Because the magnetic Prandtl number and electric contact resistance during RSW varied with the growth of the weld nugget, and the temperature-dependent properties were unavailable, he just varied the value of the two parameters to see what would happen, and found that different parameter values resulted in totally different flow patterns.…”
Section: Introductionmentioning
confidence: 99%
“…This study is to apply previous work [12,20,22] to extensively, generally, and realistically study transport processes during resistance spot welding experiencing heating, melting, cooling and freezing periods by accounting for distinct properties from solid-liquid phase transition. The nugget shape after solidification and cooling rate during freezing period, which are essentially required for analyzing microstructures of weld nugget in metallurgical and materials fields, are also presented.…”
Section: Introductionmentioning
confidence: 99%
“…It should reflect an initial drop due to the rupture of the surface film, an increase after the breakdown of contact resistance due to the heating of the workpiece, and the subsequent fall after the maximum resistance has been reached due to the growth of the nugget diameter or the increasing penetration of the electrodes into the workpiece [18]. Since electric currents spread strongly on entering the workpiece [19], the induced electromagnetic force gives rise to strong convection in the molten nugget [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…But these models did not consider the MHD behaviors in the nugget and they predicted a large temperature gradient in the weld nugget, which is inconsistent with Alcini's experimental findings that the thermal field in a weld nugget is relatively uniform [4] . In 1996, Wei [5] developed a finite difference (FD) model and analyzed the effects of MHD parameters on the flow field in a nugget, but did not present the exact values suitable for the RSW process. In 2000, Khan [6] built an FD model to study the gravity-driven fluid dynamics behaviors in a nugget and indicated that gravity alone could not cause a uniform thermal field in a nugget and the effect of the induced magnetic field should be considered.…”
Section: Introductionmentioning
confidence: 99%